The economic efficiency of using Heiferplus semen in dairy farms - Stelian Sertu; Vlad Ber (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
This work aims to increase the economic efficiency of dairy farms by improving the fecundity indicators and increasing the number of cows obtained. The research was carried out in the context in which the slaughter age of cows has decreased to 2.8 lactations, and the herds of dairy cows in our country are in a proportion of 93% held in holdings of up to 5 heads, which endangers the sustainability of these farms. In the context where 0.8% of cattle/year are obtained from a cow, of which only 0.6% are viable and according to the ratio between the sexes, only 0.3% of cattle are born and the exchange of generations in this species is high, 4.8 years , the use of new semen processing technologies is required. One of these technologies is HeiferPlus. This technology uses conventional sperm enhanced with certain enzymes that capacitate spermatozoa carrying X or Y chromosomes depending on the desired direction. The work was carried out at the Research and Development Institute for Bovine Balotesti, on a herd of 89 heads, cows of the Romanian Black Spoted breed, where the efficiency of the use of HeiferPlus semen was analyzed. From the analyzed data, an increase in fecundity was found by 4.03% and the proportion of females obtained was 57.5%. In these conditions, the use of HeiferPlus sperm is recommended because by increasing fecundity, production costs decrease by reducing calving intervals and obtaining more cattle ensures the maintenance/increase of existing herds.
Keywords: Q01; Q19; Q55; 330; economic efficiency; cows; HeiferPlus semen